2021
DOI: 10.1002/jclp.23168
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depression in aging veterans and former prisoners‐of‐war: The role of social support and hardiness

Abstract: Objectives: Depression is a prevalent outcome of traumatic experiences, such as combat and war captivity. This study explores the heterogeneity of changes over time and assesses the contribution of trauma exposure (combat vs. war captivity), hardiness, and social support for depression trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…In addition to a younger age, lower levels of education and lack of social support were also significant predictors of depression several decades after the war in a study that included prisoners from both World War II and the Korean War [21]. Other studies have also shown that lack of social support is one of the most significant predictors of developing PTSD and other psychological disorders [49,[77][78][79][80].…”
Section: Personality Vulnerability Socio-demographic Factors and Soci...mentioning
confidence: 97%
“…In addition to a younger age, lower levels of education and lack of social support were also significant predictors of depression several decades after the war in a study that included prisoners from both World War II and the Korean War [21]. Other studies have also shown that lack of social support is one of the most significant predictors of developing PTSD and other psychological disorders [49,[77][78][79][80].…”
Section: Personality Vulnerability Socio-demographic Factors and Soci...mentioning
confidence: 97%
“…In their study, Bachem and colleagues found that social support played a key role in preventing depression among veterans [7]. Similarly, in Canavan and colleagues' research, it was found that policies that encourage education, promote financial and health literacy, and strengthen families may reduce vulnerability to the mental health effects of unemployment, with social support buffering the relationship between involuntary unemployment and depressive symptoms [8].…”
Section: The Effect Of Stable Social Relationships On Patientsmentioning
confidence: 95%
“…Most commonly, these include variations upon the following trajectories: resilience (i.e., few to no symptoms following trauma exposure), recovery (i.e., clinically relevant symptoms decreasing over time), chronic (i.e., stable, high levels of symptoms over time), and delayedonset (i.e., subclinical symptoms worsening over time to severe; Armenta et al, 2019;Galatzer-Levy et al, 2018). Distinct symptom trajectories have been documented in relation to posttraumatic stress disorder (PTSD) in particular (Armenta et al, 2019;, though similar patterns have also been observed in depression and anxiety symptoms (Armenta et al, 2019;Bachem et al, 2021;L. M.-E. Hinchey, Nashef, et al, 2023).…”
mentioning
confidence: 99%